Análise do desempenho da tecnologia OFDM para os sistemas móveis de quarta geração: influência da densidade de pilotos no desempenho do sistema OFDM - Ferreira, Onésimo (2010)
The objective of this dissertation is to analyze the performance of OFDM technology for the fourth generation mobile systems. Consisting of seven chapters, it covers all the elements necessary to understand the technique based on OFDM multicarrier. The chapter 1 is introductory, and it gives a brief overview of the technologies of mobile internet access. The chapter 2 briefly shows the characteristics of channels with fading in environments with ray multipath. It is the basic knowledge to understand the phenomena that occur in these channels, and is essential for the theoretical analysis and for the evaluation of the performance, in radio channels, of the techniques based on multicarrier. The chapter 3 shows the history and the principle of multicarrier-based techniques, including OFDM technique. Includes the history from the origin until the present shape. The study discusses the use of the discrete Fourier transform, the insertion of the guard interval, the insertion of the cyclic prefix for the current form of OFDM and ends showing the parameters of OFDM system in LTE (Long Term Evolution) air interface. The chapter 4 discusses the characteristics of OFDM systems. Presents a model of the radio channel, where a transmitted signal is not only distorted by multipath fading, but also corrupted by thermal noise. Shows the relationship between the number of subcarriers, the frequency selectivity and the selectivity in time. It also shows the relationship between the length of guard interval and the frequency selectivity. Emphasizes the theoretical analysis and discusses the advantages and the disadvantages of OFDM system, including the robustness against the frequency selective fading, the robustness against the impulsive noise, the sensitivity to frequency offset, the sensitivity to nonlinear amplifications and the sensitivity to conversions A / D (analog to digital) and D / A (digital to analog). The chapter 5 presents a method to estimate the channel and the different possibilities for allocating pilots, such as allocation of pilot spaced in time and considering all the frequencies, the allocation of pilot spaced in frequency and considering full time and the allocation of the pilot spaced in time and spaced in frequency. To finish is showed the OFDM system with pilot symbols used for channel estimation. The chapter 6 discusses the simulation of OFDM platform, exploring issues such as alternatives for improving the signal-noise ratio of the system, and presents suggestions for future works. The chapter 7 presents the conclusions